INCREASING THE ABILITY TO CONVERT FRACTIONS TO PERCENT AND DECIMAL FORM WITH THE PLAYING METHOD OF THE V STUDENTS OF CLASS V SDN PERSIL - Ahyar Rasyidi; Azrul Adam Syamsu (PROGRES PENDIDIKAN, 2022)
The objectives of this research are: (1) to reveal the ability to convert fractions into percent and decimal forms and vice versa with the play method; (2) to reveal an increase in the ability to convert fractions into percent and decimal forms and vice versa by applying the playing method. This research is a qualitative research with the type of Classroom Action Research (CAR). Data was collected using the test method to collect data on student abilities and observation sheets were used to measure the effectiveness of the teaching and learning process. Based on the research results, the application of the play method can optimize teacher participation, student participation and the ability to convert fractions into percent and decimal forms and vice versa. The results of the ability to convert fractions into percent and decimal and vice versa in the first cycle reached 74.17 and reached 82.23 in the second cycle. By applying the play method in learning, it can increase the ability to convert fractions into percent and decimal forms and vice versa, this is indicated by an increase in students' abilities by 8.06.